Role of FIB-4 and eGFRcysC as Diagnostic Tools for Early Detection of Impaired Hepato-Renal Function in Chronic Alcoholics - Goyal, Piyush; Kaur, Jaskiran (Journal of Neonatal Surgery, 2025)
Aim: To evaluate the association between hepatic fibrosis, measured by the Fibrosis-4 (FIB-4) index, and renal function, assessed by cystatin C–based estimated glomerular filtration rate (eGFRcysC), in chronic alcohol-consuming patients, and to compare findings with age- and sex-matched healthy controls. Methods: Cross-sectional, case–control research was done at the Department of Biochemistry, Subharti Medical College, Meerut, between 18 months. One hundred chronic alcoholics (≥10 years; >40 g/day for males and >20 g/day for females) and 100 healthy controls were enrolled. Exclusion conditions were non-alcoholic liver disease, severe chronic kidney disease (CKD), nephrotoxic drugs, malignancy, HIV, acute sepsis, and pregnancy. Clinical information was captured and fasting blood draws assayed for liver and renal function, viral markers, and serum cystatin C. FIB-4 scores and eGFRcysC were determined. Statistical analysis was done with Student's t-test and Chi-square test with p<0.05 as significant. Results:Patients had much higher mean FIB-4 values (3.37 ± 1.40 vs 1.13 ± 0.42, p<0.001) and lower eGFRcysC (24.82 ± 7.56 vs 91.47 ± 14.98 mL/min/1.73 m², p<0.001) than controls. Cystatin C was increased in patients (2.84 ± 0.70 vs 0.96 ± 0.11 mg/L, p<0.001). Increased grades of fibrosis correlated with higher CKD stages, and there was a very strong inverse correlation between FIB-4 and eGFRcysC. Conclusion: Chronic alcohol use is associated with concurrent hepatic fibrosis and renal impairment. FIB-4 and eGFRcysC are accessible, reliable, and complementary tools for early detection of hepatorenal dysfunction, with potential to guide timely interventions in at-risk populations.